THE ROLE OF LEADERSHIP STYLE AND WORK ENVIRONMENT ON TEACHER PERFORMANCE THROUGH WORK MOTIVATION OF PUBLIC ELEMENTARY SCHOOL TEACHERS IN CARITA DISTRICT, PANDEGLANG REGENCY - Juhaeni, Ade; Rustandi, Tata; Permana, Angrian (Yayasan Education and Social Center, 2025)
1 Elementary school education is the most important educational process in student development. This is because elementary school is the source of basic education for children to acquire knowledge after they are educated by their parents at home. This study aims to determine the direct influence of leadership style and work environment on teacher performance and work motivation at SDN Carita District, Pandeglang Regency, as well as the indirect influence of both through work motivation on teacher performance. This research method is quantitative research to analyze the causal relationship between variables. This causal research uses quantitative data from a population of 60 teachers at SDN Carita District, Pandeglang Regency, with a saturated sample method. The Likert scale is used to measure respondents' attitudes and perceptions of social phenomena. The results of the study show that leadership style has a significant positive effect on teacher performance (coefficient 0.216,p-value0.007) and work motivation (coefficient 0.189,p-value0.037). The work environment has a very strong influence on teacher performance (coefficient 0.675,p-value0.000) and work motivation (coefficient 0.799,p-value0.000). Work motivation also has a significant effect on teacher performance (coefficient 0.562,p-value0.025), with an indirect influence of leadership style and work environment through work motivation. The study shows that leadership style and work environment have a positive and significant effect on teacher performance at SDN Carita District, Pandeglang Regency. Leadership style increases work motivation, which also contributes to teacher performance. The work environment has a very strong influence on motivation and performance. The indirect influence of leadership style and work environment through work motivation is also significant, confirming the importance of good management to improve teacher performance sustainably.